The effect of exchange rate movement on export earnings of palm oil products: case in Malaysia / Emilda Amir - Amir, Emilda (2016)
The study examines the effect of exchange rate movement on Malaysia's export earnings of palm oil products. The data used in monthly basis of time series which is from January 2008 to September 2015. The study applies the EGARCH model to measure the movement of exchange rate. As the conclusion, there is significant positive impact between exchange rate movements on export earnings of palm oil products.